2014
DOI: 10.1111/bph.12648
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol decreases fructose‐induced oxidative stress, mediated by NADPH oxidase via an AMPK‐dependent mechanism

Abstract: BACKGROUND AND PURPOSEOxidative stress is an important pathogenic factor in the development of hypertension. Resveratrol, the main antioxidant in red wine, improves NO bioavailability and prevents cardiovascular disease. The aim of this study was to examine whether resveratrol decreases the generation of reactive oxygen species (ROS), thereby reducing BP in rats with fructose-induced hypertension. EXPERIMENTAL APPROACHRats were fed 10% fructose with or without resveratrol (10 mg·kg ) for 1 week or for 4 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 53 publications
5
47
0
Order By: Relevance
“…In our experimental system, we have shown that AMPK activation is involved in the protective effects of resveratrol on cardiomyocytes through suppressing high glucose-induced oxidative stress. Our results was similar with previous in vivo study that resveratrol decreases fructose-induced oxidative stress mediated by NADPH oxidase via an AMPK-dependent mechanism (Cheng et al, 2014). Balteau et al suggested that NADPH oxidase activation by hyperglycemia in cardiomyocytes is independent of glucose metabolism (Balteau et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…In our experimental system, we have shown that AMPK activation is involved in the protective effects of resveratrol on cardiomyocytes through suppressing high glucose-induced oxidative stress. Our results was similar with previous in vivo study that resveratrol decreases fructose-induced oxidative stress mediated by NADPH oxidase via an AMPK-dependent mechanism (Cheng et al, 2014). Balteau et al suggested that NADPH oxidase activation by hyperglycemia in cardiomyocytes is independent of glucose metabolism (Balteau et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…pAMPK is also know to inhibit TGFβ1 signaling, which would further reduce pathologic inflammation and fibrosis [29]. Lastly, pAMPK also inhibits reactive oxygen species [30], reducing the pathologic consequences of an over active immune response even further. Therefore, the naturally increased pAMPK found in the MRL skeletal muscle tissue can inhibit HFD pathologies at multiple points.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, resveratrol microinjection into the rostral ventrolateral medulla lowered BP and heart rate by decreasing the sympathetic vasomotor tone [66], which may be mediated through NO synthesis and a decrease in Ca 2+ influx [66]. Resveratrol has also been shown to activate AMPK in the nucleus tractus solitarii (NTS) in the brainstem of fructose-fed rats [67], and it has been proposed that this activation lowers BP through decreasing ROS generation, enhancing Akt-nNOS pathway activity, and up-regulating SOD2 levels in the NTS [67].…”
Section: Accepted Manuscriptmentioning
confidence: 99%